PENGARUH PENERAPAN SISTEM AKUNTANSI KEUANGAN DAERAH (SAKD) DAN PENERAPAN GOOD GOVERNANCE TERHADAP KUALITAS LAPORAN KEUANGAN (STUDI KASUS PADA SATUAN KERJA PERANGKAT DAERAH KABUPATEN BANDUNG BARAT) - Didah Nurjanah, - (2022)
This study aims to determine the effect of the application of regional financial accounting systems and the implementation of good governance on the quality of financial reports. The population in this study is the Regional Work Unit of West Bandung Regency, amounting to 47 SKPD. The sampling method used is purposive sampling with a total of 20 Offices in the Regional Work Units. The data used is primary data. The analysis technique in this study uses multiple linear regression analysis with SPSS 23 output tool. The results show that the application of regional financial accounting systems has an effect on the quality of financial reports. While the implementation of good governance does not affect the quality of financial reports. Keywords: Regional Financial Accounting System, Good governance, Quality of Financial Reports.